The More You Care, the Worthier I Feel, the Better I Behave: How and When Supervisor Support Influences (Un)Ethical Employee Behavior - Sguera, Francesco; Bagozzi, Richard P.; Huy, Quy N.; Boss, R. Wayne; Boss, David S. (Journal of business ethics, 2018)
This article investigates the effects of perceived supervisor support on ethical (organizational citizenship behaviors) and unethical employee behavior (counterproductive workplace behavior) using a multi-method approach (one experiment and one field survey with multiple waves and supervisor ratings of employees). Specifically, we test the mediating mechanism (i.e., supervisor-based self-esteem) and a boundary condition (i.e., employee task satisfaction) that moderate the relationship between support and (un)ethical employee behaviors. We find that supervisor-based self-esteem fully mediates the relationship between supervisor support and (un)ethical employee behavior and that employee task satisfaction intensifies the relationship between supervisor support and supervisor-based self-esteem.